Whispered voice test for screening for hearing impairment in adults and children: systematic review - Pirozzo, S; Papinczak, T; Glasziou, P (BMJ Publishing Group, 2003)
Objective: To determine the accuracy of the whispered voice test in detecting hearing impairment in adults and children. Design: Systematic review of studies of test accuracy. Data sources: Medline, Embase, Science Citation Index, unpublished theses, manual searching of bibliographies of known primary and review articles, and contact with the authors. Study selection: Two reviewers independently selected and extracted data on study characteristics, quality, and accuracy of studies. Studies were included if they had cross sectional designs, at least one of the index tests was the whispered voice test, and the reference test (audiometry) was performed on at least 80% of the participants. Data extraction: Data were used to form 2x2 contingency tables with hearing impairment by audiometry as the reference standard. Data synthesis: The eight studies that were found used six different techniques. The sensitivity in the four adult studies was 90% or 100% and the specificity was 70% to 87%. The sensitivity in the four childhood studies ranged from 80% to 96% and specificity ranged from 90% to 98%. Conclusion: The whispered voice test is a simple and accurate test for detecting hearing impairment. There is some concern regarding the lower sensitivity in children and the overall reproducibility of the test, particularly in primary care settings. Further studies should be conducted in primary care settings to explore the influence of components of the testing procedure to optimise test sensitivity and to promote standardisation of the testing procedure.